Removal, Recovery and Reuse of Resource in Waste Streams: Challenges, Management and Solutions - O, Obadimu C.; A, Adelagun R.O. (Darul Yasin Al Sys, 2024)
The concept of resource recovery has received immense attention in the last decade from researchers globally due to the stringent discharge limit of nutrients, the provision of an alternative for the highly expensive inorganic fertilizers and as well as reduction of environmental pollution. Resource recovery has given wastewater a new look as a resource from which values can be derived. However, it is faced with an array of issues, ranging from technological feasibilities of recoveries, social-cultural acceptance, economic and business feasibilities, legislative-political challenges, marketability of the recovered products and environmental-ecological challenges. In this study these challenges are highlighted, considered and eval_uated for possible solutions. The technological aspects are considered in the form of the source of recovery, methods and techniques as wsell as the applicability of the recovered products. A decisive aspect is enlightenment via education to change people’s perspectives and attitudes towards the application of recovered products. Other challenges are also stated and reviewed and solutions are proffer to militate these challenges if properly considered. Finally, as there is not one single, encompassing solution for these challenges as some are localized and geographical, solutions therefore, must be tailor-made to fit and adapt to the challenge at hand.